Death by incarceration: Detention duration, overdose, and COVID-19 in Los Angeles County Jails, 2008–2023 - Adrianne Katrina Nelson; Michael Everett; Rachel Smith; Lindsey Rogers; Renee Grange; Rebekah Alfred; Haller Jackson; Lauren Woyczynski; Nikolas Brandt; Zainab Jamali; Muryam Hasan; Chanel Nejad; et al. (PLoS ONE, 2026)
Importance Jail mortality in the United States has risen sharply in recent years, yet deaths in custody—especially those related to substance use—remain underexamined. The COVID-19 pandemic and the opioid crisis compounded pre-existing carceral health issues, necessitating a closer examination of their combined impact and aftermath. Previous reports suggest that incarcerated people—particularly those who overdose on drugs—die early in their confinement. This article indicates that the dual health threats of the COVID-19 pandemic and the opioid crisis have changed this relationship, substantially extending the time from arrest to death. Objective To investigate how duration of confinement, manners and causes of death (e.g., COVID-19, substance use), and pandemic mitigation policies impacted mortality in Los Angeles (LA) County Jail from 2008–2023. Design A retrospective, observational study utilizing linked datasets to identify mortality trends and associated factors. Setting LA County Jail, the largest jail system in the United States. Participants We created three data sets: 1) LA County Jail deaths from 2008–2023, N = 509, 2) City Jail deaths within LA County, encompassing LA City Jail deaths 2008–2023, N = 42 and Non-LA City Jail deaths, 2008–2023, N = 30, and 3) all bookings from 2010–2022, N = 1,435,479. Main outcome(s) and Measure(s) Mortality trends over time, duration of incarceration prior to death, duration of incarceration for those released or transferred, and cause-specific mortality including direct standardized rates and standardized mortality ratios. Statistical models assessed the impact of confinement duration and pandemic and opioid crisis years on mortality. Results Jail mortality broadly, and substance-related deaths specifically, increased from 2008 to 2023, peaking during the pandemic. The median time from arrest to death was over five times as long (59 days) as the median duration of stay for all bookings (11 days). COVID-19 infection, prolonged confinement, and restrictive pandemic policies were associated with elevated mortality rates. Conclusions and Relevance Findings highlight the urgent need for reforms, including reduced incarceration; reduced incarceration duration; expanded access to substance use disorder treatment; decreased influx of drugs into jails; increased programming, visits, and out-of-cell time; and improved health safeguards.